Characterization and economic analysis of intensive cropping systems in rainfed lowlands of Ilocos Norte, Philippines - Lucas, M.P.; Pandey, S.; Villano, R.A.; Culanay, D.R.; Obien, S.R. (Cambridge University Press, 1999)
Many farmers are intensifying production systems by applying greater amounts of inorganic fertilizers, irrigation and pesticides, especially to cash crops. Such intensified systems, even though economically profitable in the short run, may not be sustainable. This paper analyses the economics and sustainability of an intensified rainfed rice-based system in Ilocos Norte, Philippines. Farmers use high levels of inorganic fertilizers for cash crops such as sweet pepper, garlic and tomato. Although these crops generate high levels of income, the high input systems may not be sustainable in the long run due to adverse on-site and off-site effects. Preliminary estimates of total factor productivity that include on-site effects only, display no clear time trend. However, negative externalities created by high nitrate contamination of groundwater and high rates of pesticide usage could make the system unsustainable by adversely affecting human health and the environment.